Barrio doctor: A photo essay - Mayoral, Anna Benilda M. (Animo Repository, 1994)
This thesis project entitled BARRIO DOCTOR is a black-and-white photo essay made up of 21 photographs. Orientation is in the horizontal format and all photographs are 8 X 10 inches in size. This project shows the rural medical practitioner (Dr. Victor Maniquis) as he goes around working in an area where modern medical technology is not present.